Methodological advancements in foodborne pathogen determination: from presence to behavior. (April 2016) - Greppi, Anna; Rantsiou, Kalliopi
Highlights: Gene expression at different levels can explain pathogen behavior in food or within the host. Omics technologies can provide a global view of gene expression. Biomarkers may predict the behavior of pathogens in food. Several methodologies are available to study foodborne pathogen behavior. Abstract : For biological hazards in foods, that is living organisms that interact with the environment and ultimately with the host, the choice of diagnostic tool shapes the type of information obtained and provides diverse opportunities for further management steps. In this context, food microbiology is experiencing a progressive shift from methods that determine the presence/absence or concentration of pathogenic microorganisms in food toward methods that provide information regarding the 'physiological state' of microorganisms. This shift is continuously accelerated as a consequence of technological advancements in molecular biology methods that nowadays reach unprecedented depth of biological information in a single experiment or from a single sample. The focus now is to understand foodborne pathogen behavior throughout the food chain and its impact in disease causing potential.